Effect of multimodal preventive analgesia based on serratus anterior plane block and oxycodone on postoperative analgesia in elderly patients undergoing thoracoscopic lobectomy: a randomized controlled trial - Yaru Huang; Feifei Qin; Zhongming Lian; Zhiwei Ge; Xiaohang Sun; Jianjun Yang; Dandan Tian (Scientific Reports)
Abstract Patients undergoing thoracoscopic lobectomy often experience significant postoperative pain, which is frequently inadequately managed in elderly patients due to their unique physiological characteristics. Multimodal preventive analgesia has been shown to provide satisfactory pain relief and promote early recovery. The objective is to optimize perioperative pain management in elderly patients by multimodal preventive analgesia through a combination of serratus anterior plane block (SAPB) and oxycodone. A total of 80 elderly patients with lung cancer undergoing elective uniportal video-assisted thoracoscopic lobectomy under general anesthesia were enrolled, classified as American Society of Anesthesiologists (ASA) II or III, were randomly assigned to four groups. Group M1 received ultrasound-guided SAPB with 0.375% ropivacaine combined with intravenous oxycodone. Group M2 received intravenous oxycodone. Group M3 received SAPB, while the control group (Group C) was included for comparison. The primary outcome measures included the Visual Analogue Scale (VAS) scores at rest and during coughing immediately after postoperative tracheal extubation. Secondary outcome measures comprised VAS scores at rest and during coughing at 6 h, 24 h, 48 h, and 72 h postoperatively; intraoperative remifentanil consumption; number of activations of the Patient-Controlled Intravenous Analgesia (PCIA) pump; frequency and dosage of rescue analgesia; intraoperative vasoactive drug consumption; and incidence of postoperative adverse events. The experimental groups had significantly lower VAS scores compared to the control group at all measured time points. In the M1 group, VAS scores at 6 h and 24 h after surgery were significantly lower than those in the other two experimental groups. The secondary outcomes are statistically significant differences among the four groups. Multimodal preventive analgesia based on SAPB and oxycodone can effectively reduce perioperative pain in elderly patients undergoing thoracoscopic lobectomy, decrease intraoperative and postoperative opioid consumption, and facilitate recovery. Trial registration: ChiCTR2400088399.